Multiple enhancer regions govern the transcription of CCN2 during embryonic development - Frost, S; Liu, K; Li, I; Poulet, B; Comerford, E; De Val, S; Bou-Gharios, G (Springer Netherlands, 2017)
CCN2 is a critical matricellular protein that is expressed in several cells with major implications in physiology and different pathologies. However, the transcriptional regulation of this gene remains obscure. We used the Encyclopaedia of DNA Elements browser (ENCODE) to visualise the region spanning from 300 kb upstream to the CCN2 start site in silico in order to identify enhancer regions that regulate transcription of this gene. Selection was based on three criteria associated with enhancer regions: 1) H3K4me1 and H3K27ac histone modifications, 2) DNase I hypersensitivity of chromatin and 3) inter-species conservation. Reporter constructs were created with sequences spanning each of the regions of interest placed upstream of an Hsp68 silent proximal promoter sequence in order to drive the expression of β-galactosidase transgene. Each of these constructs was subsequently used to create transgenic mice in which reporter gene production was assessed at the E15.5 developmental stage. Four functional enhancers were identified, with each driving distinct, tissue-specific patterns of transgene expression. An enhancer located -100 kb from the CCN2 transcription start site facilitated expression within vascular tissue. An enhancer -135 kb upstream of CCN2 drove expression within the articular chondrocytes of synovial joints. The other two enhancers, located at -198 kb and -229 kb, mediated transgene expression within dermal fibroblasts, however the most prevalent activity was found within hypertrophic chondrocytes and periosteal tissue, respectively. These findings suggest that the global expression of CCN2 during development results from the activity of several tissue-specific enhancer regions in addition to proximal regulatory elements that have previously been demonstrated to drive transcription of the gene during development.